Pengendalian Folikulogenesis Ovarium dengan Pemberian Ekstrak Biji Kapas - Siska Adelya Ramadhani; Iman Supriatna; Ni Wayan Kurniani Karja; Adi Winarto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Gosipol is a substances contained in extracted cotton seed which is thought to have the antifertility ability therefore it is often used as a herbal contraceptive. The aim of this study were to assess the folliculogenesis in mice after administrated with cottonseed extract. 60 female mice strain DDY which was 14-15 weeks old and 30-35 g body weight were divided into five groups and given cottonseed extract each 0; 1,5; 2,1 and 2,7 g/kg BW for 5, 10, 15, 24, and 24 + 10 days (without cottonseed treatment). At the end of the treatment period, mice was euthanasia to observe follicular development histomorphology (each three mice of each treatment). Mice estrous status were evaluated based on the description of the vaginal smear cells with Giemsa staining. The results showedthat the number of developing follicles was low (P < 0.05) compared with control after 5 days cottonseed extract administration at dose 2,7 g/kg BW that were 23 ± 3,6. At dose 1,5 and 2,1 g/kg BW the number of follicles was low after 24 days that were 25 ± 10,4 and 27 ± 3,5. Recovery effects of follicle number after cottonseed extract administration for 24 days was the best at a dose of 1,5 g/kg BW. Prolonge of estrous cycle occured in mice which were administrated the cottonseed extract of at all dose treatment. In conclusion, although the decrease in the number of developing follicles and prolonge of estrous cycles occurred after cottonseed extract administration, but these effects are reversible after the administration ended.